La3B14−: an inverse triple-decker lanthanide boron cluster. Issue 54 (19th June 2019) - Chen, Teng-Teng; Li, Wan-Lu; Chen, Wei-Jia; Li, Jun; Wang, Lai-Sheng
Abstract : The relationship between the global minima of a tilted inverse triple-decker La3 B14 − and a perfect inverse triple decker La⋯B8 ⋯La⋯B8 ⋯La. Abstract : We report the observation of the first inverse triple-decker complex in a tri-lanthanide-doped boron cluster. Photoelectron spectroscopy of La3 B14 − reveals well-resolved photodetachment transitions. Quantum chemical studies show that the most stable structure of the La3 B14 − cluster exhibits a tilted La–B8 –La–B8 –La inverse triple-decker structure with two conjoined B8 rings sharing a pair of B atoms due to strong inter-layer B–B bonding. The tilted structure enhances both B–B and B–La bonding, resulting in a highly stable inverse triple-decker structure. Theoretical calculations further show that multi-decker conjoined structures are viable as a new class of 1D lanthanide boron nanostructures.